2016
DOI: 10.1111/bjd.14887
|View full text |Cite
|
Sign up to set email alerts
|

Invasive melanomain vivocan be distinguished from basal cell carcinoma, benign naevi and healthy skin by canine olfaction: a proof-of-principle study of differential volatile organic compound emission

Abstract: Invasive melanoma in vivo releases odorous VOCs distinct from those of BCC, benign naevi and healthy skin, adding to the evidence that the volatile metabolome of melanoma contains diagnostically useful biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…It was decided to begin a series of double-blind tests. However, after 13 runs, the dog had successfully identi ed only one of the melanoma samples (44). Implementing blinded conditions is not easy during training because dog handlers need to know when to reinforce positive behaviour.…”
Section: Atmospheric Conditionsmentioning
confidence: 99%
“…It was decided to begin a series of double-blind tests. However, after 13 runs, the dog had successfully identi ed only one of the melanoma samples (44). Implementing blinded conditions is not easy during training because dog handlers need to know when to reinforce positive behaviour.…”
Section: Atmospheric Conditionsmentioning
confidence: 99%
“…Other investigators have walked off the beaten paths and reported unconventional findings, for example Willis et al . investigated a dog's olfactory ability to discriminate melanoma from control skin lesions . In this study, a Labrador, named Ronnie, performed 20 double‐blind tests, each requiring the selection of one melanoma from nine controls, consisting of three each of basal cell carcinomas, naevi and healthy skin.…”
Section: Braaff Scoring System For Pigmented Lesionsmentioning
confidence: 99%
“…Similarly, many studies reported that dogs can detect the presence of early-stage cancer in their owners through odor. Consequently, dogs are being trained for cancer detection [9,10]. In the same manner, the current researchers investigated the relationship between skin gas and the effects of diet, physical condition, and aging in healthy volunteers, instead of people suffering from illnesses or disorders.…”
Section: Introductionmentioning
confidence: 99%